Macerated-Pineapple Core Crude Extract-derived Bromelain Has Low Cytotoxic Effect in NIH-3T3 Fibroblast - Dewi Liliany Margaretta; Angliana Chouw; Yanni Dirgantara; Melanie Sadono Djamil; Ferry Sandra (The Indonesian Biomedical Journal, 2015)
BACKGROUND: Bromelain is a sulfhydryl proteolytic enzyme that can hydrolyze protein, protease or peptide. Bromelain can be found in pineapple stem, fruit and core. Bromelain is composed of 212 amino acid residues with cysteine-25 forming a polypeptide chain that can hydrolyze peptide bonds by H2O. In medicine, bromelain has been developed as antibiotic, cancer drug, anti-inflammatory agent and immunomodulator. In dentistry, bromelain has potential to reduce plaque formation on the teeth and to irrigate root canal.METHODS: Pineapple core was dried for 3 days to get simplicia. Then simplicia was extracted with water solvent for 24 hours. After that, the macerated-pineapple core crude extract-derived bromelain (PCB) was separated by Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) followed by Coomassie Brilliant Blue (CBB) staining to ensure the presence of bromelain. In cytotoxic test, NIH-3T3 fibroblast cultures were treated with extracts in various concentrations to for 24 or 48 hours. Number of fibroblasts was calculated using 3-(4,5-dimethylthiazol-2- yl)-2,5-Diphenyltetrazolium bromide (MTT) assay.RESULTS: Pineapple core extraction using maceration method produced relative high yield (concentration: 1.5424 g/mL) of bromelain, which was confirmed by CBB staining results with the molecular weight of 33 kDa. Based on cytotoxic test results of PCB on NIH-3T3 fibroblasts, 24-hours-incubation LD50 was 95.7 g/L, while 48-hours-incubation LD50 was 51.1 g/L.CONCLUSION: PCB has low cytotoxic effect in NIH-3T3 fibroblasts.KEYWORDS: bromelain, pineapple, extract, cytotoxic, MTT